Use of Waste & Recycled Material in Construction & Its Applications - Kumar, Tarun (Gyan Management Journal, 2020)
The primary objective of this research review is to find the possible utilization of different reused and waste material and for final supply of those materials for Construction. As we are producing waste in tones day by days so we need to utilize that waste in some different and efficient manner so that we can reduce that threat to environment.We are increasing loads on nation’s landfills as well. For economicviability andto find best solution for environment we can utilize the waste products and can reuse them after suitable modification in their properties we can use them as some foreign to enhance the mechanical, chemical and other properties of the building in addition to construction material. By using these materials in construction we can reduce load on Nations landfills as well.Reuse of waste materials helps to preserve natural resources, save energy, helps in to decrease solid waste, reduction in pollution levels and other factors which effects our environment directly. Construction companies can being aware and they can take the advantage by using these waste and recycled material. This review paper discusses the implications caused due to various waste products and features their reusing possibilities and conceivable use for producing good construction material. This paper deals with proper use of waste and recycled material in construction and application in this field.